Peran Budaya Siri’ dalam Pengambilan Keputusan Perkawinan Suku Mandar Perspektif Al Urf (Studi Desa Bonde Kecamatan Campalagian Kabupaten Polewali Mandar) - Munawara; Ahmad Izuddin (Jurnal Ragam Pengabdian, 2026)
Siri’ culture is a fundamental life principle upheld by the Mandar Tribe, particularly in Bonde Village, Campalagian District, Polewali Mandar Regency. It functions as an unwritten social norm that guides community behavior, including in marriage decision-making. In the mabottoi sorong phase, which determines the dowry and related obligations, the principle of siri’ is central. Customary rules regulate these elements, including the dowry and Chinese peputiq, which symbolize family honor and self-esteem. This study aims to deepen understanding of siri’ culture and examine it from the perspective of ‘urf in Islamic law. This research uses a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Informants were selected using purposive and snowball sampling, involving arayyang (noble families), religious leaders, and cultural figures who understand siri’ traditions. Relevant literature also supports the analysis. The findings indicate that siri’ culture qualifies as ‘urf sahih (valid custom) because it provides social benefits and aligns with Islamic values. It reinforces modesty, dignity, and self-respect, particularly for women, and supports the appropriateness of dowry arrangements in marriage according to Islamic principles.